2010
DOI: 10.1007/s10198-009-0213-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health care expenditure on sickness absence

Abstract: Increased health care expenditure could be used to improve quality of care or reduce waiting time and could therefore be expected to a¤ect health and sickness absence of a population. Still, based on data from a panel of the Swedish municipalities, public health care expenditure was found to have no or a negligible e¤ect on absence due to sickness or disability. The same result was obtained when separate estimates were done for men and women and for absence due to sickness and disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…They demonstrated that an increase in government expenditure on education and healthcare contributed to an increase in the number of people attending school and a reduction in mortality rates for infants and children. Several studies have examined the impact of government healthcare expenditures on health outcomes [25][26] . Many researchers have also assessed the impact of private healthcare expenditures [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that an increase in government expenditure on education and healthcare contributed to an increase in the number of people attending school and a reduction in mortality rates for infants and children. Several studies have examined the impact of government healthcare expenditures on health outcomes [25][26] . Many researchers have also assessed the impact of private healthcare expenditures [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…The GNIpc for all of the included countries was divided by 1000 to standardize this value for comparisons. Second, health spending defined as the percentage of the total gross domestic product spent on health expenditures was also added in the models because it is considered a significant explanatory variable for health outcomes in previous studies [ 29 , 30 ]. Although the relationship between health care expenditures and health outcomes is conflicting according to how health outcomes are defined, we decided to include health care expenditure in the models because we thought it might be a mediating variable between civic participation and health.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the importance of public health and disease prevention is not foreign to health policy makers. Researchers have paid a significant amount of attention to public health expenditures (Brown, 2014;Brown et al, 2014;Duggan, 2000;Rivera, 2001;Self and Grabowski, 2003;Glick and Menon, 2009;Potrafke, 2010;Granlund, 2010;Herwartz and Theilen, 2014;Bailey and Goodman-Bacon, 2015), non of which explore the effect on hospital efficiency. Brown (2014) and Brown et al (2014) Research focusing on public health primarily analyzes the impact of public health expenditures, typically on an aggregated health measure.…”
Section: Public Health and Health Care Expendituresmentioning
confidence: 99%